The manifestation of Islamization of knowledge (IOK) in the curriculum : a case study of International Islamic University Malaysia - Maulana, Mohammad Firman (Institute of Education, International Islamic University Malaysia, 2014)
This research is aimed at investigating the manifestation and implementation of Islamization of Knowledge (IOK) in the curriculum of three institutions at the International Islamic University Malaysia (IIUM); Institute of Education (INSTED), Psychology Department and Sociology and Anthropology Department. The manifestation of IOK should emerge in the operation of education such as in its objectives of the curriculum and syllabus, course contents, methods and evaluation system. Qualitative case study was employed as the method to arrive at the conclusions of the study. Document analyses, observations and interviews with six lecturers and 15 students from the related institutions had been conducted. Focus group interview was conducted with the students in three groups and each one comprised of five students upon which data were analyzed by employing thematic analysis by using colour coding. The findings indicate that the Islamic dimension had been infused in the curriculum design at each institution where the participants indicated various ways to inculcate IOK in their teaching and learning activities. Whatever used by the lecturers intentionally combined, harmonized and integrated the epistemological views in a positive manner. In this sense, the education system was in accordance with the philosophy, mission and vision of the university. The eclectic approach was the one most utilized by the lecturers to constructively criticize some elements which were not in line with the Islamic worldview. Meanwhile, the comparative approach was considered the best and the most effective method to present the knowledge which was Islamic-based and the conventional knowledge, which was secular-based. However, lecturers' awareness, skills, knowledge, expertise and capability were required to eclectically merge various sources of knowledge from revelation (wahy) and human sources. The terms used such as harmonization, contextualization, relevantization or de-westernization principally represented the Islamization efforts, and in this context, the epistemological field. The participants perceived that their institutions had significantly endeavoured to utilize the IOK. Nevertheless, to make the agenda more effective it needs more professionalism in management and control mechanism with an authoritative approach from the top leaders of the university. The IOK committee at each institution for example, should be more active in organizing the programmes, training, workshops and alike, as well as more concerned in mediating and facilitating the academicians, in particular to participate and stress on the IOK as a crucial issue in the educational activities